Situational Juvenile Deliquency Effects in Lucia Priandarini’s Novel “Dua Garis Biru” - Iin Almeina Lubis (International Journal Labs, 2022)
Juvenile delinquency is an act that violates the rules, laws or norms in society that are carried out at the age of adolescence or the transition from childhood to adulthood or entering the age of 10-12 years and ending at the age of 18-22 years. The purpose of this study is to explain the effects situational juvenile deliquency in the Lucia Priandarini’s novel Dua Garis Biru. The method used in this research is a qualitative approach. The data that is collected from a qualitative research is typically extracted through research methods such as observations, case studies, interviews and videotapes. Data to be analyzed using qualitative research. Specific methods might include content analysis and thematic analysis. The impact of sex free in the novel is the same as what happens in society, where many teenagers have free sex and suffer the consequences such as pregnancy outside of marriage, early marriage, and abortion.